A SYSTEMATIC LITERATURE REVIEW ON THE DETERMINANTS OF UMRAH PILGRIMS’ SATISFACTION - Salsabillah; Handoko, Luqman Hakim (Multazam : Jurnal Manajemen Haji dan Umrah, 2025)
The objective of this study is to explore the available research that discusses the conditions and perspectives surrounding Umrah pilgrims’ satisfaction, find out what factors affect the satisfaction of Umrah pilgrims in using travel services published on Google Scholar, and create a conceptual model related to what factors affect the satisfaction of Umrah pilgrims. The study employs secondary data consisting of research articles related to the satisfaction of Umrah pilgrims. The research adopts a descriptive qualitative methodology combined with the PRISMA analytical framework for systematic reviews. The results demonstrate that the highest number of relevant publications appeared in 2023, totaling three scientific studies. Factors that determine congregation satisfaction include six variables: service quality, trust, facilities, pricing, price and promotion.